2012
DOI: 10.1530/eje-11-0662
|View full text |Cite
|
Sign up to set email alerts
|

Serum high-mobility group box-1 levels are positively associated with micro- and macroalbuminuria but not with cardiovascular disease in type 1 diabetes: the EURODIAB Prospective Complications Study

Abstract: Context and objective: High-mobility group box-1 (HMGB1) is a pro-inflammatory cytokine that may contribute to the pathogenesis of micro-and macrovascular complications commonly observed in diabetes. We investigated whether HMGB1 is associated with: i) markers of low-grade inflammation (LGI) and endothelial dysfunction (ED) and pulse pressure (PP, a marker of arterial stiffness); ii) prevalent nephropathy, retinopathy and cardiovascular disease (CVD) in type 1 diabetes; and iii) the potential mediating roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…Second, an inter-assay variation lower than 11%, as obtained in our HMGB1 measures, may enable more precise estimates of the associations examined. Third, we have recently shown that in patients with type 1 diabetes (EURODIAB study) serum HMGB1 was not associated with prevalent CVD [10]. Apart from the difference in study design (cross-sectional vs prospective), the apparent discrepancy with the positive association between plasma HMGB1 and incident CVD observed in the present study raises the possibility that measures obtained in serum vs plasma may not represent the same pool of HMGB1.…”
Section: Discussioncontrasting
confidence: 67%
“…Second, an inter-assay variation lower than 11%, as obtained in our HMGB1 measures, may enable more precise estimates of the associations examined. Third, we have recently shown that in patients with type 1 diabetes (EURODIAB study) serum HMGB1 was not associated with prevalent CVD [10]. Apart from the difference in study design (cross-sectional vs prospective), the apparent discrepancy with the positive association between plasma HMGB1 and incident CVD observed in the present study raises the possibility that measures obtained in serum vs plasma may not represent the same pool of HMGB1.…”
Section: Discussioncontrasting
confidence: 67%
“…Although it was originally believed that the innate immune system is activated only in response to pathogens like bacteria and viruses, it is now widely accepted that endogenous molecules generated during sterile injury have equal capacities in activating immunity, which actually evolved to react to danger and not just to non–self-threats (9,20,21). Thus, activation of TLRs is a process that has now been documented as initiating or perpetuating the chronic low-level systemic inflammation that characterizes chronic sterile conditions, such as diabetes (9,14,19,2224). …”
Section: Discussionmentioning
confidence: 99%
“…In patients with type 1 diabetes, serum HMGB1 levels were positively associated with markers of low-grade inflammation and endothelial dysfunction. In addition, higher serum HMGB1 levels were associated with greater prevalence and severity of albuminuria [40]. Activation of HMGB1/RAGE signaling axis is important in promoting proinflammatory pathways considered to play an important role in diabetes-induced retinal vascular inflammation.…”
Section: Discussionmentioning
confidence: 99%